Penatalaksanaan Fisioterapi Pada Kasus De Quervain Syndrome Sinistra Di RSUD Salatiga - Wardani S, Ike Rossyam; , Agus Widodo, S.Fis., M.Fis (2015)
Background: De Quervain syndrome is the cause of most of the tendonopathy wrist. In these conditions there is inflammation of the tendons on the thumb tenosynovium dorsal part, abductor longus and extensor policis policis brevis. This tendon is under the extensor retinaculum located along the processus styloideus radii.. Problems of physiotherapy which can be found in the case of which is pain in the area of motion in the wrist and hand, decreased range of motion (LGS) at the metacarpophalangeal joint (MCP), decreased muscle strength, and functional limitation that functional limitations in ADL. Methods: method in handling such cases ultrasound (US) and exercise therapy, which was evaluated by measuring pain mete d out (VDS), the measurement of muscle strength (MMT), the measurement of LGS (goneometer) and ADL capability (WHDI). Objectives: the above method to determine the benefits of the therapy modalities and therapeutic exercise in the US to reduce pain, increase range of motion, increased muscle strength and increased ability ADL. Results: after 6 times treatment showed a decrease in pain, increase in LGS thumb the left, the left thumb MMT increase and the increased capacity of functional activity. Conclusion: US can reduce pain in such cases. While exercise therapy can improve the LGS, increase muscle strength and functional ability.